POTRET PELAKSANAAN PROGRAM PENDIDIKAN INKLUSIF - Azizah, Nur; Khatima, Asmahusnul; Auliyah, Nurhasana; Ansar, Ahlun; Arismunandar, Arismunandar (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Inclusive education is an approach that provides equal learning opportunities for all students, including children with special needs, in mainstream schools. This study aims to analyze the implementation of the inclusive education program at SD Inpres Maccini Baru, Makassar. The method used in this study was qualitative through observation and in-depth interviews with the principal. This study focused on school policies, the admission process for students with special needs, curriculum adjustments, supporting facilities, the role of Special Assistant Teachers, as well as challenges faced by the school and strategies to overcome them. The findings of this study indicate that the school has implemented planned and collaborative inclusive education, although there are still shortcomings in the number of assistants and facilities. Collaboration between teachers, parents, and the community is a crucial element in the success of the inclusive program at the school. The results of this study are expected to serve as guidelines for the development of inclusive education in other elementary schools and contribute to improving the quality of educational services that enable all students to learn without discrimination. ABSTRAKPendidikan inklusif adalah sebuah pendekatan yang memberikan kesempatan belajar yang setara bagi semua siswa, termasuk anak-anak dengan kebutuhan khusus, di sekolah-sekolah umum. Penelitian ini bertujuan untuk menganalisis pelaksanaan program pendidikan inklusif di SD Inpres Maccini Baru, Makassar. Metode yang digunakan dalam penelitian ini adalah kualitatif melalui observasi dan wawancara mendalam dengan kepala sekolah. Fokus kajian ini adalah pada kebijakan sekolah, cara penerimaan siswa berkebutuhan khusus, penyesuaian kurikulum, fasilitas yang mendukung, peran Guru Pendamping Khusus, serta tantangan yang dihadapi sekolah dan strategi untuk mengatasinya. Temuan dari penelitian ini menunjukkan bahwa sekolah telah melaksanakan pendidikan inklusif secara terencana dan kolaboratif, meskipun masih ada kekurangan dalam jumlah tenaga pendamping dan fasilitas. Kerja sama antara guru, orang tua, dan komunitas menjadi unsur penting dalam keberhasilan program inklusif di sekolah. Hasil penelitian ini diharapkan bisa menjadi pedoman untuk pengembangan pendidikan inklusif di sekolah dasar lainnya dan memberikan kontribusi terhadap peningkatan kualitas layanan pendidikan yang memungkinkan semua peserta didik belajar tanpa diskriminasi.